Stress and its impact on elite athletes' wellbeing and mental health—a mini narrative review - Nuetzel, B. (Frontiers in Sports and Active Living, 2025)
Within the context of elite sports, the term "health" is tantamount to maximum physical performance. From the very beginning of their athletic careers, elite athletes are trained to prioritize performance over health in order to be successful. To reach the top and competitive goals, they often cannot avoid situations that might be endangering their health. A career in elite sports means that elite athletes must take extreme health risks and at the same time protect their health to continuously deliver peak performances. According to Fletcher and Hanton, psychological research is confronted with a particular challenge because elite athletes are subject to numerous stressors both during and after their sports career. The examination of the relevant stress-related factors (relationships, competitive pressure, defeat, injuries, etc.) points to a growing body of evidence signifying that these factors could be responsible for mental health problems in the target population. Because these challenges are multidimensional in nature, a comprehensive understanding of this topic's complexity is required. To obtain an understanding of stressors and resources in elite sport, the author performed a narrative mini review of 3 databases covering studies published up to 2023.